If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + 4x = 6x + -35 Reorder the terms: 30 + 4x = -35 + 6x Solving 30 + 4x = -35 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 30 + 4x + -6x = -35 + 6x + -6x Combine like terms: 4x + -6x = -2x 30 + -2x = -35 + 6x + -6x Combine like terms: 6x + -6x = 0 30 + -2x = -35 + 0 30 + -2x = -35 Add '-30' to each side of the equation. 30 + -30 + -2x = -35 + -30 Combine like terms: 30 + -30 = 0 0 + -2x = -35 + -30 -2x = -35 + -30 Combine like terms: -35 + -30 = -65 -2x = -65 Divide each side by '-2'. x = 32.5 Simplifying x = 32.5
| 9x*-12x+4=0 | | -1(x-6)=8x-12 | | 8p-28=-22+9p | | 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a | | 432=x(x-6)(x-6) | | -5p+8+6p=10 | | x+3x=4x | | .5x-1.5=-6.5 | | (180x-1800)/(x)(x-20) | | 3x-45-3x= | | x=5/8y | | Y^2+9=6y | | 38=0.4n | | 3n+2+1=-21 | | 7+(4+4)= | | 0.3x=26 | | x1/10 | | 11=x-5+8 | | 3n+2+1=-2 | | x(x-6)(x-2)=996 | | 49w=-8 | | 8(x-2)=2x+8 | | 15t-14=-14 | | 9=-5r-4r | | -1(x-6)= | | 8x^2+2x+9=0 | | -9(6n+4)=18-5n | | 2(6x+6)= | | 2=4k-5k |